Prevalence of Clostridium perfringens toxin genotypes in enterotoxemia suspected sheep flocks of Andhra Pradesh - N. Vinod Kumar; D. Sreenivasulu; Y. N. Reddy (Veterinary World, 2014)
Aim: To identify the Clostridium perfringens toxin genotypes prevailing in enterotoxemia suspected sheep flocks in Andhra Pradesh by using multiplex PCR. Materials and Methods: Intestinal scrapings were collected from lambs below three months of age from flocks with similar management from different Districts of Andhra Pradesh, in India. A total of 208 samples were collected with 140 from enterotoxemia suspected flocks and 68 from healthy flocks. Following processing and culture of the samples, colonies were identified by morphological and biochemical tests. All the clostridial isolates were analyzed by multiplex PCR. Results: C. pefringens were isolated from 97 out of 140 enterotoxemia suspected flocks (69.29%) and 27 out of 68 healthy flocks (39.71 %). Genotyping of the 97 iolates by multiplex PCR from enterotoxemia suspected flocks indicated C. perfringens type A, C and D 67.01% (65 out of 97); 11.34% (11 out of 97) and 21.65% (21 out of 97) respectively. Isolates from healthy flocks indicated the presence of type A and D 92.59% (25 out of 27) and 7.40% (2 out of 27) respectively. Number of isolates from enterotoxaemia suspected flocks were significantly high (P<0.001) than healthy flocks. Type A is found to be predominant in both enterotoxemia suspected and healthy flocks (67.01% and 92.59%). Conclusions: Prevalence of C. perfringens type C was reported for the first time in India. Clostridium perfringens type D and type C were found to be the major causative types for enterotoxemia.